Biology and significance of leptin in animal production: A perspective - A MUKHERJEE; I SAMANTA; S N JOARDAR (Indian Journal of Animal Sciences, 2023)
Leptin, an adipocyte-derived cytokine (adipokine) has plethora of physiological roles in the body, particularly in the onset of puberty, viz. reproduction and immune function of an animal. Moreover, body fatness which is a crucial determinant of meat quality is governed by blood leptin level. Since its discovery in 1994, various research groups have explored its potential role in animal production, reproductive fitness and immune function which ultimately determine the profitability of livestock rearing. Leptin binds with leptin receptor (LEPR) and activates different intracellular signaling pathways to activate downstream gene expression process to execute its functions. Intensive research works have shed light on the central role of this molecule in intricate circuitry of nutrition, metabolism, energy homeostasis and immune response. Single nucleotide polymorphisms (SNPs) detected on promoter or exon or intron region of leptin gene has been found to be associated with various key traits of animal productivity. The present review focusses to summarise about this gene structure and function in domestic mammalian species and need of future research efforts on leptin and related pathways for augmenting production of farm animals.